Rapid decline of resting heart rate trajectories from childhood to young adulthood is paradoxically associated with increased cardiac mass. Issue 10 (22nd November 2021) - Hao, Guang; Halbert, James; Su, Shayong; Bagi, Zsolt; Robinson, Vincent; Thayer, Julian; Harshfield, Gregory; Kapuku, Gaston
Abstract: Background: Little is known about the varied resting heart rate (RHR) trajectory patterns from childhood to young adulthood and their clinical significance. We aim to identify RHR trajectories from childhood to young adulthood, and to determine their relationship with left ventricular mass (LVM) index. Methods: RHR was measured up to 15 times over a 21-year period in 759 participants from childhood to young adulthood. LVM was measured using echocardiography and was normalised to body surface area to obtain LVM index in 546 participants. Results: Using latent class models, three trajectory groups in RHR from childhood to young adulthood were identified, including high-decreasing group (HDG), moderate-decreasing group (MDG), and low-decreasing group (LDG). We found that trajectory of RHR was a significant predictor of LVM index with faster decrease of RHR associated with higher levels of total peripheral resistance ( P for trend <0.001) and LVM index ( P for trend <0.001). Compared to the LDG, individuals in the HDG showed higher LVM index ( β = 6.08, p < 0.001). In addition, the interactions between race and RHR trajectories for LVM index was significant ( p < 0.05). Conclusion: Our findings show an association between RHR trajectories from childhood to young adulthood with cardiac mass, suggesting that monitoring RHR may help identify subpopulation at high cardiovascular risk.